2020
DOI: 10.1021/acs.orglett.0c01078
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Total Synthesis of the Dimeric Naphthoquinonopyrano-γ-lactone (−)-Crisamicin A: Introducing the Dimerization Site by a Late-Stage Hartwig Borylation

Abstract: The first stereoselective total synthesis of the dimeric naphthoquinonopyrano-γ-lactone (−)-crisamicin A was realized (13 steps, 5% overall yield). 1,4,5-Trimethoxynaphthalene, reached in five known steps, was brominated at C-3 to install a but-3-enoic ester by an ensuing Heck coupling. An asymmetric Sharpless dihydroxylation followed and gave a β-hydroxy-γ-lactone with >99.9% ee. Its OH substituent and acetaldehyde established the dihydropyran ring in a completely diastereoselective oxa-Pictet−Spengler cycliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Oxidation of 3a using Oxone gave phenolic derivative 7 in near-quantitative yield, which we expect to serve as a convenient basis for generating new BTD-based push–pull systems. Boronic ester 3a also underwent oxidative Pd-catalyzed homocoupling 36 to the heterobiaryl system 8 , which has been of interest recently as a component of electrochromic polymers. 37 The synthesis of 8 previously proceeded by condensation of SOCl 2 and 3,3′,4,4′-tetraaminobiphenyl.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation of 3a using Oxone gave phenolic derivative 7 in near-quantitative yield, which we expect to serve as a convenient basis for generating new BTD-based push–pull systems. Boronic ester 3a also underwent oxidative Pd-catalyzed homocoupling 36 to the heterobiaryl system 8 , which has been of interest recently as a component of electrochromic polymers. 37 The synthesis of 8 previously proceeded by condensation of SOCl 2 and 3,3′,4,4′-tetraaminobiphenyl.…”
Section: Resultsmentioning
confidence: 99%
“…γ‐Butyrolactone is a very common unit in natural products and drugs. [ 6 ] For example, n ‐butylphthalide (NBP) is a marketed antiplatelet drug for ischemia‐cerebral apoplexy. [ 7,8b ] Canonne's group used 3‐hydroxyisobenzofuran‐1(3 H )‐one and n ‐butyl magnesium bromide to afford NBP.…”
Section: Resultsmentioning
confidence: 99%
“…Different strategies have been proposed for the total synthesis of crisamacin due to its medicinal and biological applications [ 113 ]. Kopp et al [ 114 ] in 2020 reported the total synthesis of crisamicin A by carrying out Sharpless asymmetric dihydroxylation, oxa-Pictet–Spengler cyclization, Heck coupling and Hartwig borylation. Total synthesis began with the generation of 262 by Heck coupling of 259 and 261, which were prepared independently from compounds 258 and 260 .…”
Section: Review Of the Literaturementioning
confidence: 99%